Constructing a novel carbon skeleton to anchor Sn/SnO2 nanodots for flexible supercapacitor with excellent rate capability. (July 2022) - Li, Zhen; Zhang, Chenying; Bu, Jingting; Zhang, Long; Cheng, Lingli; Wu, Minghong
Abstract: Designing SnO2 /carbon composites is an effective strategy to improve the conductivity and buffer the volume expansion of SnO2 . However, it remains a challenge to combine SnO2 and carbon materials tightly as a stable integration. Herein, a facile and versatile strategy of Sn/SnO2 nanodots anchored tightly into carbon nanofibers (CNFs) with the decoration of graphene quantum dots (GQDs) for high performance supercapacitor is reported. Through a simple electrospinning and carbonization reduction process, a novel multidimensional carbon skeleton of GQD/CNF effectively improves the conductivity, and importantly, abundant Sn–O–C covalent bonds are constructed to anchor SnO2 nanodots tightly into GQD/CNF, suppressing SnO2 aggregation and facilitating electron/ion transfer kinetics. Consequently, as self-supporting and binder-free electrode material, Sn/SnO2 /GQD/CNF displays high specific capacitance of 168.6 mA h g −1 (1349 F g −1 ) at 1 A g −1 with excellent rate capability (88.9% retention at 20 A g −1 ). Furthermore, a flexible solid-state asymmetric supercapacitor based on Sn/SnO2 /GQD/CNF and GQD/CNF achieves a high energy density of 32.3 W h kg −1 at a power density of 800 W kg −1 with remarkable flexibility and cycling stability (86.1% retention after 5000 cycles). The excellent electrochemical performances demonstrate that this novel carbon skeleton anchored active materials shows great potential for electrochemical energy storage applications. Graphical abstract: Image 1